2022
DOI: 10.3389/ijph.2022.1605113
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Acceptability Among Healthcare Facility Workers in Sierra Leone, the Democratic Republic of Congo and Uganda: A Multi-Centre Cross-Sectional Survey

Abstract: Objectives: This cross-sectional survey explored COVID-19 vaccine acceptability among public healthcare facility workers in Kambia (Sierra Leone), Goma (Democratic Republic of Congo) and Masaka (Uganda).Methods: Questionnaire-based interviews conducted between April–October 2021 explored participants’ knowledge and perceptions of, and attitudes towards, the COVID-19 pandemic and COVID-19 vaccines, as well as COVID-19 vaccine acceptability (defined as uptake of ≥1 dose or intent to get vaccinated).Results: Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Based on the included studies in this review, the intention rate to uptake the COVID-19 vaccine among HCWs was below average [ 23 , 25 , 46 , 47 , 54 , 59 , 76 , 77 , 80 , 83 , 88 ]. Conversely, fourteen studies reported an above-average intention rate [ 48 , 49 , 51 , 52 , 55 , 60 , 69 , 71 , 79 , 82 , 88 , 91 , 92 ]. The overall average intention rate for HCWs to uptake the COVID-19 vaccines across all included studies was approximately 52%, indicating a suboptimal level of uptake among this population.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the included studies in this review, the intention rate to uptake the COVID-19 vaccine among HCWs was below average [ 23 , 25 , 46 , 47 , 54 , 59 , 76 , 77 , 80 , 83 , 88 ]. Conversely, fourteen studies reported an above-average intention rate [ 48 , 49 , 51 , 52 , 55 , 60 , 69 , 71 , 79 , 82 , 88 , 91 , 92 ]. The overall average intention rate for HCWs to uptake the COVID-19 vaccines across all included studies was approximately 52%, indicating a suboptimal level of uptake among this population.…”
Section: Resultsmentioning
confidence: 99%
“…Within the theme of COVID-19 vaccines, ten sub-themes were identified, all acting as barriers to vaccine uptake. The most prominent sub-theme was safety concerns, which was reported as the primary barrier [ 23 , 25 , 43 , 47 , 50 , 51 , 55 , 56 , 57 , 60 , 61 , 65 , 66 , 67 , 68 , 69 , 70 , 72 , 74 , 75 , 76 , 77 , 78 , 81 , 82 , 83 , 84 , 85 , 86 , 88 , 90 , 91 , 92 , 95 ]. However, only three studies mentioned confidence in the COVID-19 vaccines, facilitating uptake [ 47 , 52 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations